Development of Language in the Profits Participants Based on Age - Risalatul Muazizah (ELite Journal : International Journal of Education, Language, and Literature, 2019)
The aim of this study is to find and describe the development of language mastery in the essay of students seen from the aspect of the number of entries, affix, spelling, and code change. To achieve these objectives, qualitative and quantitative methods are used. The data obtained are three articles of children, adolescents, and adults with one theme and the same time. The results of this study indicate that there is an increase in the number of entries, affixes, spelling use, and code changes in each age group. A prominent difference exists in the use of affixes and spelling in articles. Each age group uses different affixes. For example, children often use prefix {meN-}, adolescents use prefix {ber-}, and suffix {-nya}, whereas adults have more affix variations. The results of this study can help teachers and community to know the characteristics of the development of language mastery in the essay of learners based on their age.. Keywords: authorship, learners, age